Wogonin Ameliorates Renal Inflammation and Fibrosis by Inhibiting NF-κB and TGF-β1/Smad3 Signaling Pathways in Diabetic Nephropathy - Zheng Z; Zhu W; Lei L; Liu X; Wu Y (Dove Medical Press, 2020)
Zhi-chao Zheng, Wei Zhu, Lei Lei, Xue-qi Liu, Yong-gui Wu Department of Nephrology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of ChinaCorrespondence: Yong-gui WuDepartment of Nephrology, The First Affiliated Hospital of Anhui Medical University, No. 218, Jixi Road, Hefei, Anhui 230032, People’s Republic of ChinaTel +86 0551 6292 2111Email wuyonggui@medmail.com.cnIntroduction: Diabetic nephropathy (DN) has become an increasing threat to health, and inflammation and fibrosis play important roles in its progression. Wogonin, a flavonoid, has been proven to suppress inflammation and fibrosis in various diseases, including acute kidney injury. This study aimed at investigating the effect of wogonin on diabetes-induced renal inflammation and fibrosis.Materials and Methods: Streptozotocin (STZ)-induced diabetic mouse models received gavage doses of wogonin (10, 20, and 40 mg/kg) for 12 weeks. Metabolic indices from blood and urine and pathological damage of glomerulus in the diabetic model were assessed. Glomerular mesangial cells SV40 were cultured in high glucose (HG) medium containing wogonin at concentrations of 1.5825, 3.125, and 6.25 μg/mL for 24 h. Inflammation and fibrosis indices were evaluated by histopathological, Western blotting, and PCR analyses.Results: Wogonin treatment ameliorated albuminuria and histopathological lesions in diabetic mice. Inflammatory cytokines, such as monocyte chemotactic protein-1 (MCP-1), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and related signaling pathway NF-κB were downregulated after the administration of wogonin in vivo and in vitro. Furthermore, wogonin reduced the expression of extracellular matrix (ECM), including fibronectin (FN), collagen IV (Col-IV), α-smooth muscle actin (α-SMA), and transforming growth factor-β 1 (TGF-β 1) in the kidneys of diabetic mice and HG-induced mesangial cells. Moreover, the inhibition of TGF-β 1/Smad3 pathway might be responsible for these changes.Conclusion: Wogonin may ameliorate renal inflammation and fibrosis in diabetic nephropathy by inhibiting the NF-κB and TGF-β 1/Smad3 signaling pathways.Keywords: diabetic nephropathy, wogonin, inflammation, fibrosis